Measurement of the B+→ωl+ν and B+→ηl+ν branching fractions - Aubert, B; Bona, M; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Garra Tico, J; Grauges, E; Lopez, L; Palano, A; et al. (2009)
We present a study of the charmless semileptonic B-meson decays B+→ωl+ν and B+→ηl+ν. The analysis is based on 3.83×108 BB̄ pairs recorded at the Υ(4S) resonance with the BABAR detector. The ω mesons are reconstructed in the channel ω→π+π-π0 and the η mesons in the channels η→π+π-π0 and η→γγ. We measure the branching fractions B(B+→ωl+ν)=(1.14±0.16stat±0. 08syst)×10-4 and B(B+→ηl+ν)=(0.31±0.06stat±0. 08syst)×10-4. © 2009 The American Physical Society.